A Survey of the Potential Ectomycorrhizal Fungi Associated With Nursery Seedlings of Seven Species of Exotic Quercus in China. (19th May 2021) - Jin, Wei; Wang, Yuchen; Sun, Haijing; Yuan, Zhilin
ABSTRACT: Seven species of Quercus have been introduced into China from the United States for their ecological and economic values. The beneficial association between Quercus trees and ectomycorrhizal (ECM) fungi is well recognized. However, the ECM fungal communities associated with these exotic oak trees grown in new environments are currently unknown. The aims of this work were to investigate the mycorrhizal status of nursery seedlings and identify the fungal communities in them. All Quercus tree species examined exhibited well-developed ECM roots. However, neither the morphology nor the color of the observed ECM types was distinctive, suggesting reduced ECM fungal diversity. The combined application of isolation and amplicon-based sequencing approaches revealed that the mycorrhizal taxa represented 5 orders and 12 genera in the Basidiomycota, but only the dominant genus Scleroderma (Boletales) was detected by both approaches. In addition, Scleroderma exhibited the lowest degree of host specificity, but relatively high interspecific genetic diversity. Isolates assigned to Sistotrema displayed taxonomic novelties based on sequence similarity searches against the GenBank database. Non-metric multidimensional scaling analysis showed a degree of differentiation of ECM communities among Quercus species. Our results provide insights into the identities of exotic Quercus -associated ECM fungi and will improve symbiosis-based seedling nursing technology.